Control and manipulation of cold atoms in optical tweezers - Muldoon, C (2012)
The ability to address and manipulate individual information carriers in a deterministic, coherent, and scalable manner is a central theme in quantum information processing. Neutral atoms trapped by laser light are amongst the most promising candidates for storing and processing information in a quantum computer or simulator, so a scalable and flexible scheme for their control and manipulation is paramount. This thesis demonstrates a fast and versatile method to address and dynamically control the position (the motional degrees of freedom) of neutral atoms trapped in optical tweezers. The tweezers are generated by using the direct image of a Spatial Light Modulator (SLM) which can control and shape a large number of optical dipole-force traps. Trapped atoms adapt to any change in the potential landscape, such that one can re-arrange and randomly access individual sites within atom-trap arrays. A diffraction limited imaging system is used to map the intensity distribution of the SLM onto a cloud of cold atoms captured and cooled using a Magneto Optical Surface Trap (MOST).